Policy Perspectives and Student Teachers’ Perceptions towards B.Ed. Programme - Yadav, Moni; Singh, Sunita (JOURNAL OF INDIAN EDUCATION, 2023)
Teacher education programmes occupy a significant place in the education system, which encompasses teaching skills, pedagogical, theoretical, and practical understanding along with necessary professional skills to the student teachers through a variety of programmes like B.Ed., B.El.Ed., D.El. Ed. and others. Its curriculum includes many foundational and perspectives papers such as sociological, philosophical, and psychological, along with different pedagogical disciplines and liberal arts. These perspectives and foundation papers create a holistic and reflective teacher. The purpose of this study was to explore the perceptions of student teachers toward teacher education programmes and their nature, various aspects and approaches of the teacher education curriculum, which were categorised as perspectives in education, disciplinary and pedagogical understanding, and their engagement with the field—self, community, and school. Through purposive sampling, 47 participants (student teachers) were taken as samples from the second year of the B.Ed. programme. The researcher opted for descriptive survey design. A self developed perception scale was used for the collection of data, and Cronbach’s alpha reliability (internal consistency) was measured as 0.841. Percentage analysis was used for data analysis. The study revealed that most of the student teachers are in favour of the curriculum, pedagogy, and engagement with self, school and community. It also demonstrates that this two-year course is well organised in terms of theoretical and practical practices for their professional development and develops them as reflective practitioners.